2010
DOI: 10.1002/ppul.21174
|View full text |Cite
|
Sign up to set email alerts
|

Associations of tonsillar hypertrophy and snoring with history of wheezing in childhood

Abstract: Children with history of wheezing have more frequently tonsillar hypertrophy than those without wheezing. Tonsillar hypertrophy may mediate at least in part the reported association between asthma and obstructive sleep-disordered breathing in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 38 publications
0
38
0
1
Order By: Relevance
“…20 Therefore, the small amount of residual lymphoid tissue left after ITA may be enough to compromise the airway. While individual response to ETA or ITA is likely mul- 31 Several studies [32][33][34][35] have confirmed that patients with asthma are more likely to develop symptoms of OSAS. A recent study 36 also found that after adenotonsillectomy, children with asthma had a significant reduction in asthma exacerbation, hospitalization, and emergency department visits.…”
Section: Overnight Psgmentioning
confidence: 96%
“…20 Therefore, the small amount of residual lymphoid tissue left after ITA may be enough to compromise the airway. While individual response to ETA or ITA is likely mul- 31 Several studies [32][33][34][35] have confirmed that patients with asthma are more likely to develop symptoms of OSAS. A recent study 36 also found that after adenotonsillectomy, children with asthma had a significant reduction in asthma exacerbation, hospitalization, and emergency department visits.…”
Section: Overnight Psgmentioning
confidence: 96%
“…[53][54][55] Wheezing can be interpreted as a surrogate for asthma, 56 however, asthma at age 7 was not found to be a predictor of HS. It could also be interpreted as a sign of URIs, 57 however, early URIs were not significant for HS.…”
Section: Discussionmentioning
confidence: 99%
“…As rationale, the association between wheezing and SDB has been supported [50,51] and wheezing was predictive of physician-diagnosed asthma in this cohort [52], a known risk factor for SDB [43,50,53]. Further, the association between snoring and asthma has been found to be independent of allergic rhinitis, which is often linked to asthma [53].…”
Section: Support Of Cluster Clinical Validitymentioning
confidence: 93%
“…Further, the association between snoring and asthma has been found to be independent of allergic rhinitis, which is often linked to asthma [53]. As further rationale, both wheezing and snoring have been linked with adenotonsillar hypertrophy [43,51], and adenotonsillectomy is known as the first line treatment for SDB [21].…”
Section: Support Of Cluster Clinical Validitymentioning
confidence: 99%